Immunological, mediated with IgE and associated with herpesvirus infection, phenotypes of nephrotic syndrome among children - R. A. Belovolova; G. M. Letifov; L. V. Mavrina; E. V. Belovolova; A. P. Titov; E. V. Churyukina; L. F. Ovsyannikova (Аллергология и Иммунология в Педиатрии, 2023)
The development of nephrotic syndrome (NS) among children is accompanied by the observable changes of the immune status, which are manifested by the disbalance of lymphocytes subpopulations, dysimmunoglobulinemia and the disturbance of the metabolic activity of phagocytes. Immunological, associated with higher level of total IgE and HVI phenotypes of nephrotic syndrome among children were identified. NS of hyper IgE-phenotype is characterized by the increase of general IgE level in the peripheral blood. NS associated with HVI is characterized by the activation of humoral antiherpetic immunity, which was manifested by the presence of active HVI markers in the blood (Ab IgM and/or Ab IgG of low avidity to VH) on the background of clinical manifestations of HVI: the presence of fever, lymphadenopathy, enlargement of liver and spleen, skin and mucous rashes. The addition of antivirus drugs to the standard basic treatment of NS stopped the clinical signs of HVI exacerbation and optimized NS therapy.